Edukasi PHBS dalam Upaya Peningkatan Derajat Kesehatan Masyarakat di Tatanan Rumah Tangga - Sukanty, Ni Made Wiasty; Yunita, Lina; Rahmiati, Baiq Fitria; Astawan, Wanda Januar; Septian, Defel (LPPM Universitas Bumigora, 2023)
Clean and healthy living behavior (PHBS) in the household is one of the government's programs to improve people's welfare. PHBS indicators in homes include using clean water, washing hands with soap and clean water, and using healthy latrines. Lack of knowledge and public awareness of the importance of PHBS and inadequate health support facilities and infrastructure can be a factor causing high rates of morbidity and mortality due to a disease. One of the means of supporting public health is the availability of water sources. The decrease in river water discharge in Lembah Sari Village can affect sanitation related to PHBS in the community. We have conducted PHBS counseling activities in Lembah Sari Village using PowerPoint media, posters, and teaching aids. It was an effort to help people know, want, and practice PHBS. After receiving counseling, the community became more aware of PHBS. The community seemed enthusiastic and participated in practicing washing hands with soap as an indicator of PHBS. This activity is expected to be applied by the community daily.